Changes in butterfly species richness (Lepidoptera: Papilionoidea) over two decades in the Koroška region, Northern Slovenia - Vid Švara; Rudi Verovnik (Natura Sloveniae)
Changes in butterfly fauna in the Koroška region in northeastern Slovenia have been compared over a period of 22 years. Records from 12 sampling sites from late July 2016 are compared with the same sites from late July/early August 1994. On average, 30% of species richness was lost per site, with a maximum loss of 80% at one site with complete habitat degradation. Records from 35 sampling sites from July 2016 are presented, including records of several rare habitat specialist species, such as Lycaena dispar, Plebejus optilete, Boloria titania, and Phengaris arion, the latter being of particular importance for conservation. All in all, habitat degradation has been confirmed to be the main driver of the loss of butterfly richness in the Koroška region.